(untitled) (International Journal of Innovative Technologies in Economy, 2018)
The article substantiates the need to improve the known technologies of managing changes in society in general and within its separate socio- economic subsystems by introducing the technology of reengineering the mentality of human resources as a compulsory component of these processes. The main reason of occurrence of unpreparedness and even resistance to implementation changes of human resources of socio-economic systems in the processes of management of changes, determined by the "path dependency problem" that arise in the processes of transformation of society and its components due to the differentiation of ideological, political and the economic views of the participants, as demonstrated by the example of alternative and dominant-complementary institutional matrices of the western and eastern type. It is demonstrated that for conditions and requirements of the society of a new economy it is more appropriate to interpret the institutional matrix as a result of the union of two dominant-complementary matrices in the form of a rhombus, or diamond, the ideological and economic setups of the sides of which will form such changes in the mentality of human resources of modern socio-economic systems that will not be conflicting, which requires a reengineering of the mentality of human resources, ahead of the development and implementation of key organizational, social, technical and technological changes. The working definition of the concept of "reengineering the mentality" of human resources is proposed and it is established that for its large-scale introduction into the management of changes it is necessary to master the leading personnel of systems by ideological and economic installations of a new diamond-like institutional matrix